Microbiorobotics : biologically inspired microscale robotic systems - Kim, Minjun; Steager, Edward; Agung, Julius (Amsterdam ; Boston : Elsevier ; Waltham, MA : William Andrew, 2012)
Microbiorobotics is a new engineering discipline that inherently involves a multidisciplinary approach (mechanical engineering, cellular biology, mathematical modeling, control systems, synthetic biology, etc). Building robotics system in the micro scale is an engineering task that has resulted in many important applications, ranging from micromanufacturing techniques to cellular manipulation. However, it is also a very challenging engineering task. One of the reasons is because many engineering ideas and principles that are used in larger scales do not scale well to the micro-scale. For example, locomotion principles in a fluid do not function in the same way, and the use of rotational motors is impractical because of the difficulty of building of the required components. Microrobotics is an area that is acknowledged to have massive potential in applications from medicine to manufacturing. This book introduces an inter-disciplinary readership to the toolkit that micro-organisms offer to micro-engineering. The design of robots, sensors and actuators faces a range of techology challenges at the micro-scale. This book shows how biological techniques and materials can be used to meet these challenges. World-class multi-disciplanry editors and contributors leverage insights from engineering, mathematical modeling and the life sciences - creating a novel toolkit for microrobotics.
Introduction -- Fundamentals of Cellular Mechanics -- Theoretical Microbiorobotics -- Experimental Microbiorobotics -- Perspectives and Outlook.
Includes bibliographical references and index.
Keywords: Microrobots; Bioengineering; TECHNOLOGY & ENGINEERING -- Robotics; Bioengineering; Microrobots